“Celular sim! Toda hora não!”: práticas discursivas sobre o uso de dispositivos móveis na escola. - Silva Filho, Marco Antônio Medronha da (2018)
Mobile devices tend to be restricted or prohibited in some schools, mainly to students, through regulations that reinforce discourses based on a possible “dispersion” or “educational uselessness”, associated with these digital technological artifacts. This study aimed to examine the problematic and productive dimension of the use of cellphones/smartphones in the school environment, highlighting the pedagogical and social possibilities of digital culture for the teaching and learning in Sciences. The “experience” with the research subjects of the study outlined the methodological path, evidencing the singularities in the relations of each individual in the proposed space-time of action (LARROSA, 2002). Thus, what followed was the analysis of the answers of 12 teachers and 19 students of an 8th grade class of a public primary school that were generated from the application of electronic forms (VASCONCELLOS-GUEDES & GUEDES, 2007), filled in online and, consequently, this made it possible to identify their opinions on the use of digital media (focus on smartphones) in the school environment. At the same time, a video containing a “research challenge” was also produced so that the students could access it on the internet through the use of an augmented reality tool entitled QR Code (LOPES JÚNIOR et al., 2012; PRENDES, 2015), relating it with the Sciences contents studied. The proposed activity confirmed the ability that young people have to make use of digital technologies, a main hallmark of the youth culture, as well as the challenges and possibilities for the field of education. Equivalent opinions were found among the participants of the study regarding the use of mobile devices in school, classified as “attention dispersants” in class, evidencing the importance of mediation by teachers in activities that use smartphones as a pedagogical tool. Educators and students allied to a creative process can contribute effectively to the idea that other teaching strategies be implemented through the use of digital technologies in the school environment and teacher training.